Design of the solar water heating system for local communities in Pakistan - Muhammad Sadiq; Ahmad T. Mayyas (Cleaner Engineering and Technology, 2022)
Solar thermal energy has great importance in the improvement of active solar-powered systems. Performance evaluation of such systems is very complex due to the involvement of many operational factors. This study aims at evaluating the design of solar water heating systems (SWHS) for the residential sector. For a realistic estimation of design parameters, ASHRAE clear-sky-model is applied to assess solar energy potential, and then the SWHS performance is evaluated. The Scatter Search heuristic approach is applied to determine maximum solar thermal energy generation with the minimum possible total cost of the system, subject to several real-time constraints of the study area. The general-purpose optimization model is formulated, and here it is applied to the case study of a typical residential building of Islamabad, Pakistan. The results indicate the optimum system cost of 61000.14 PKR with a 6 m2 collector area and 150 L TES tank. Maximum efficiency of 59.8% is possible to be achieved such that 6.68 kWh heat energy remains for the provision of hot water during non-sunshine hours. 150 L water would be available at the end of sun-shine hours at a temperature of 54.16 Co. The impact of mass flow rate, irradiation, and temperature on collector efficiency is performed through sensitivity analysis. Realistic estimations are important to attract the masses towards the venerated benefits of such innovated technologies and would be of great importance in selecting such systems for a particular residence having a specific load.